2020
DOI: 10.1177/0973801020920096
|View full text |Cite
|
Sign up to set email alerts
|

Is the Relationship Between Government Spending and Private Consumption in Egypt Symmetric?

Abstract: The aim of this study, using Egyptian data from 1970 to 2016, is to explore the relationship between government spending and private consumption spending and to understand whether the relationship between the two is symmetric. The study uses the autoregressive distributed lag (ARDL) approach to explore a cointegration relationship between the two variables, and the nonlinear autoregressive distributed lag (NARDL) approach to test the hypothesis of a symmetric relationship between the two variables. By applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…b-Research and studies related to the impact of these remittances on the economies of the countries receiving the labor, such as the Gulf Cooperation Council (GCC) countries, especially the KSA, which are rare. Alkhathlan (2013) focused on determining the nature of the relationship between economic growth and ELR in the KSA during the 1970-2010 period using the ARDL method and an error correction model. The results of that study showed that there was a negative relationship between economic growth and ELR in the short and long term.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…b-Research and studies related to the impact of these remittances on the economies of the countries receiving the labor, such as the Gulf Cooperation Council (GCC) countries, especially the KSA, which are rare. Alkhathlan (2013) focused on determining the nature of the relationship between economic growth and ELR in the KSA during the 1970-2010 period using the ARDL method and an error correction model. The results of that study showed that there was a negative relationship between economic growth and ELR in the short and long term.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…The findings show that government consumption negatively affects private consumption therefore government consumption does not stimulate aggregate demand in ECOWAS countries. Almosabbeh (2020) analyzed the relationship between government spending and private consumption and concluded that the effect of government spending on household spending was not significant in the long run, although the two variables were substitutable for the other with a coefficient of 0.8699 which is quite high. Relationships and aggregation are caused by positive shocks to government spending [12].…”
Section: -Literature Reviewmentioning
confidence: 99%
“…Almosabbeh (2020) analyzed the relationship between government spending and private consumption and concluded that the effect of government spending on household spending was not significant in the long run, although the two variables were substitutable for the other with a coefficient of 0.8699 which is quite high. Relationships and aggregation are caused by positive shocks to government spending [12]. Dawood & Francois (2018) conducted a panel analysis at the level of 24 African countries examining the relationship between private consumption and public consumption which showed that private and government consumption are Edgeworth's substitutes [13].…”
Section: -Literature Reviewmentioning
confidence: 99%
“…The NARDL model separates the asymmetric effects of positive and negative shocks and is used for a small sample size. In addition, this model could not be applied for the second-order integral series (Almosabbeh, 2020;Kassi, Sun, Ding, Rathnayake, & Assamoi, 2019). This study used the NARDL approach for its ability to examine the asymmetric effect of the independent variable on the dependent variable (the effect of an asymmetric exchange rate fluctuation on money demand).…”
Section: Non-linear Ardl Approach (Nardl)mentioning
confidence: 99%